Tocopherol and Tocotrienol contents of chicken nuggets blended with red Palm oils before and after frying - Nurkhuzaiah, K; Babji, A.S.; Wan Rosli, W. I.; Foo, S.P. (Malaysian Palm Oil Board, 2015)
Tocopherols and tocotrienols content before and after frying in chicken nuggets blended with red palm oils NVRO, NVRO-100 and NVRO-50 was compared against the chicken fat treatment used as control. The lowest total tocopherols and tocotrienols content after frying was observed in control samples and the highest was in NVRO-100. Control samples showed significant increase of total tocopherols and tocotrienols from 34.32 ug g-1 before frying to 429.29 ug g-1 after frying due to oil uptake during frying where the cooking oil used was palm oil with inherent vitamin E precursors. The NVRO-50 showed significant decrease from 795.72 μg g-1 before frying to 690.87 μg g-1 after frying. Chicken nuggets blended with NVRO-100 were more heat stable followed by chicken nuggets blended with NVRO and NVRO-50. There was a significant loss of γ-T and δ-T in all samples after frying. This study showed the potential of utilising natural vitamin rich red palm oils as animal fat analogues in improving the nutritional quality of meat products.